The modified posterior thoracotomy for esophageal atresia - Mohamed Oulad Saiad (Wolters Kluwer Medknow Publications, 2017)
Aims: Right dorsolateral thoracotomy with splitting or sparing the latissimus dorsi is the standard approach to the esophageal atresia. The thoracoscopic approach to the treatment of esophageal atresia is a demanding procedure used only by few surgeons in few centers. The purpose of this study is to present the modified posterior thoracotomy for neonates with esophageal atresia. Patients and Methods: Between January 2007 and May 2016, the modified posterior thoracotomy was performed in 56 neonates with esophageal atresia. Results: The modified posterior thoracotomy preserves the latissimus dorsi and the thoracodorsal nerve. Neither the latissimus dorsi nor the serratus anterior is mobilized or skin flaps elevated. Satisfactory exposure, functional, and cosmetic results were obtained. No complication related to the approach was encountered. Conclusion: The modified posterior thoracotomy is a reliable approach in the treatment of esophageal atresia in neonates.